2023
DOI: 10.1089/brain.2022.0047
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Chemical Imaging Identifies Amyloid Peptide Signatures of Neuritic Plaques and Dystrophy in Human Sporadic Alzheimer's Disease

Abstract: Objective: Alzheimer's disease (AD) is the most common neurodegenerative disease. The predominantly sporadic form of AD (sAD) is age-related, but the underlying pathogenic mechanisms remain not fully understood. Current efforts to combat the disease focus on the main pathological hallmarks, in particular beta-amyloid (Aβ) plaque pathology.According to the amyloid cascade hypothesis, Aβ is the critical early initiator of AD pathogenesis. Plaque pathology is very heterogeneous, where a subset of plaques, neuriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This makes MALDI IMS a powerful tool for studying changes associated with Alzheimer’s disease at cellular resolution. Recent studies targeting the tissue microenvironment of amyloid plaques have observed various molecular signatures, distinct lipid accumulations, and even monitored Aβ-peptide content within and around β-amyloid plaques ( Casadonte et al, 2015 ; Kaya et al, 2018 ; Michno et al, 2018 , 2021 , 2022 ; Kelley et al, 2020 ; Koutarapu et al, 2022 ). The Hanreider group used MALDI combined with plaque staining to identify molecular heterogeneous plaques in a mouse model of AD and identified differential lipid signatures across multiple stages of plaque development ( Michno et al, 2022 ).…”
Section: Tools For Spatial Omics Ii: Molecular Imagingmentioning
confidence: 99%
“…This makes MALDI IMS a powerful tool for studying changes associated with Alzheimer’s disease at cellular resolution. Recent studies targeting the tissue microenvironment of amyloid plaques have observed various molecular signatures, distinct lipid accumulations, and even monitored Aβ-peptide content within and around β-amyloid plaques ( Casadonte et al, 2015 ; Kaya et al, 2018 ; Michno et al, 2018 , 2021 , 2022 ; Kelley et al, 2020 ; Koutarapu et al, 2022 ). The Hanreider group used MALDI combined with plaque staining to identify molecular heterogeneous plaques in a mouse model of AD and identified differential lipid signatures across multiple stages of plaque development ( Michno et al, 2022 ).…”
Section: Tools For Spatial Omics Ii: Molecular Imagingmentioning
confidence: 99%
“…We demonstrate the potential of the method toward delineating chemical traits of amyloid beta (Aβ) plaque pathology, the main pathological hallmark of Alzheimer’s disease (AD), in a transgenic mouse model (tgAPPSwe). We and others have been demonstrating the potential of MSI to interrogate Aβ pathology in human brain and mouse models. , Herein, we demonstrate our novel chemical imaging strategy to identify multimodal imaging signatures associated with structurally heterogeneous Aβ plaque pathology at the micrometer scale. This is important as structural plaque heterogeneity has been associated with heterogeneous, clinical presentation of AD, such as cognitive performance, while the underlying chemical traits remain unclear. …”
Section: Introductionmentioning
confidence: 97%
“…The pathology and dynamics of senile plaque formation and remodeling, as well as the precise involvement of amyloid deposition, are not fully understood, although senile plaques remain the main therapeutic targets in the development of new alternatives to prevent or reverse the disease [ 7 , 8 , 47 ]. Aβ peptides in their different aggregation states and compact senile plaques are neurotoxic both in AD and in experimental models [ 48 ] and have been associated with synaptic loss and the development of neuritic dystrophies [ 49 , 50 , 51 ]. Compact senile plaques have also been associated with abnormal curvature of nearby neurites [ 52 , 53 , 54 ] and may alter cortical synaptic integration [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%